EVALUASI SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS DANA PROGRAM BANTUAN OPERASIONAL SEKOLAH (BOS) AFIRMASI PADA SEKOLAH DASAR NEGERI (SDN) DI KABUPATEN SELUMA - Pebriansyah, Redho; Hilal Perdana Kusuma, Fathul; Mahrina, Helvoni (Jurnal Ilmu Akuntansi, 2023)
This study aims to determine the evaluation of the accounting system for cash receipts and disbursements of Affirmation School Operational Assistance Funds (BOS) at State Elementary Schools (SDN) in Seluma Regency. This type of research is descriptive qualitative, namely research that describes how the evaluation of the accounting system for cash receipts and disbursements of the Affirmation BOS program funds at SDN in Seluma Regency. The samples in this study were public elementary schools (SDN) in Seluma Regency that received affirmation BOS funds, namely SDN 131, SDN 180 and SDN 86 in Seluma district. The type of data used in this study is qualitative data. Sources of data used in this study are primary and secondary data sources collected through direct interviews. The results of this study indicate that the accounting system for cash receipts and disbursements of affirmative BOS funds at SDN in Seluma district has been running effectively and in accordance with PERMENDIKBUD No 16 of 2021.